Hormonal Responses to Synthetic Luteinizing Hormone and Follicle Stimulating Hormone-Releasing Hormone in Man. Issue 5821 (29th July 1972) - Besser, G. M.; McNeilly, A. S.; Anderson, D. C.; Marshall, J. C.; Harsoulis, P.; Hall, R.; Ormston, B. J.; Alexander, L.; Collins, W. P.
Abstract : The effects of the gonadotrophin-releasing hormone, synthetic decapeptide luteinizing hormone/follicle stimulating hormone-releasing hormone (LH/FSH-RH), have been studied in 18 normal men and five women in the follicular phase of their menstrual cycle. Rapid and dose-dependent (25 to 100 μg) increases in serum immunoreactive LH were seen, which reached a peak 20 to 30 minutes after a rapid intravenous injection. Similar but much smaller increases in serum immunoreactive FSH were seen. These conclusions have been validated by using two different immunoassay systems for each hormone. The LH/FSH-RH therefore causes both LH and FSH release in man as in animals but does not affect growth hormone, thyrotrophin, or ACTH. The gonadotrophin responses were the same in the women as in the men but were insufficient in the men to cause statistically significant changes in the serum levels of the gonadal steroid hormones, testosterone or oestradiol, or in their precursors 17 α-hydroxyprogesterone or progesterone. In the women, however, there was a rise in oestradiol after the 100-μg doses. The use of LH/FSH-RH will provide an important test to define the level of the lesion in hypogonadal patients and also should be valuable in the treatment of some types of male and female infertility. A simple and clinically useful LH/FSH-RH test of pituitary function is described (100 μg given intravenously), and the provisional normal responses of LH and FSH at 20 and 60 minutes are given.